A novel process to separate the eggshell membranes and eggshells via flash evaporation - CHI,Yuan (2022)
Abstract Eggshell membrane is a kind of cheap, abundant resources with great potential utilization value. A variety of active ingredients in it can be used as raw materials for medicine, light industry and other industries. At present, soluble protein, collagen, keratin, sialic acid, hyaluronic acid and antimicrobial protein have been successfully extracted from eggshell membrane and exploited in various fields. This study aimed to separate the eggshell membrane for fully exploiting the potential utilization value of the eggshell, and reduce the amount of waste discharged, which is conducive to protecting the ecological environment on which we depend. In order to reduce energy consumption of eggshell membrane separation, separate eggshell membranes from eggshells by flash evaporation was investigated. The flash separation conditions were optimized considering three independent variables at three different levels by response surface methodology. The results showed that the processing parameters of separating eggshell membranes and eggshells with flash evaporation were 1.0 Mpa pressure, 45% moisture content, and 5 mm eggshells’ particle size. Under these conditions, the separation rate was 69.16%. Therefore, flash separation can be a promising approach for separating eggshells and eggshell membranes.